Keragaman Peserta Didik dan Target Kurikulum di Sekolah Dasar - Darmawan, Puguh; Sa'diyah, Halimatus (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
Differentiated learning is one form of teacher effort in meeting the needs of students during learning, especially in terms of learning readiness, student learning profiles, talents and interests of students. So that teachers who apply differentiated learning are expected to achieve the target of fulfilling an independent curriculum, namely giving freedom to students who have diverse abilities to develop their talents and interests to achieve the target of the Pancasila learner profile which is targeted in the independent curriculum. This research aims to achieve the curriculum target through differentiated learning based on learner diversity. This article uses the literature review research method. The results show that the purpose of differentiated learning applied by teachers is to classify learning by paying attention to students' readiness and interest in learning, goals to be achieved, motivation, learning outcomes and respect for diversity. The implementation of differentiated learning aims to create an active, interactive and participatory learning process. During the learning process by providing different treatments in the classroom, it provides opportunities for students to learn more effectively and efficiently by classifying each of the diverse needs of students. Such as ability to learn, interest in learning and motivation to learn so that teachers can determine the right method to achieve learning goals. In addition, teachers must increase learners' interest in learning both in quantity and quality to achieve effective learning targets.